Weakness and progressive muscle tightness diagnosed as Kennedy disease - Behnam, Behdad; Arab Ahmadi, Mehran; Ashrafi, Farzad (International Clinical Neuroscience Journal, 2016)
Kennedy disease is a rare X-linked neurodegenerative disorder that affects patients in 30-50 years of age. It is caused by CAG-repeat in androgen receptor gen. There is no known effective treatment for Kennedy disease. We report a 60-year-old man who had fasciculations and proximal and distal muscle weakness. Physical examination showed involvement of the bulbar musculature accompanied by tongue atrophy and perioral muscle weakness. Furthermore, he had bilateral gynecomastia. Laboratory and imaging findings were normal, except electromyography that showed chronic proximal and distal denervation. Finally, the patient diagnosed with Kennedy disease according to clinical presentation and EMG abnormality that confirmed with genetic study.